Strengthening Brand Image through Integrated Marketing Communication: A Case Study of Sekolah Kak Seto's Approach to Educational Service Marketing - Tiara, Shofi; Dian Fordian (Universitas Yudharta Pasuruan, 2025)
Introduction: This study aims to analyze the marketing communication strategies implemented by Sekolah Kak Seto in an effort to enhance the institution's brand image. The research is motivated by the growing importance of integrated marketing communication in shaping a positive public perception of educational institutions, particularly amid increasingly competitive conditions. The research question formulated is: